2014
DOI: 10.1186/s12917-014-0308-2
|View full text |Cite
|
Sign up to set email alerts
|

First molecular detection and characterization of herpesvirus and poxvirus in a Pacific walrus (Odobenus rosmarus divergens)

Abstract: BackgroundHerpesvirus and poxvirus can infect a wide range of species: herpesvirus genetic material has been detected and amplified in five species of the superfamily Pinnipedia; poxvirus genetic material, in eight species of Pinnipedia. To date, however, genetic material of these viruses has not been detected in walrus (Odobenus rosmarus), another marine mammal of the Pinnipedia clade, even though anti-herpesvirus antibodies have been detected in these animals.Case presentationIn February 2013, a 9-year-old h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
4
6
0
Order By: Relevance
“…The novel herpesvirus DNApol sequences described here from fin whale and common minke whale were most closely related to DNApol sequences from other cetacean herpesviruses. This is consistent with previous observations that herpesvirus phylogenetic branching resembles that of its hosts [ 27 , 33 – 35 ].…”
Section: Case Presentationsupporting
confidence: 93%
See 1 more Smart Citation
“…The novel herpesvirus DNApol sequences described here from fin whale and common minke whale were most closely related to DNApol sequences from other cetacean herpesviruses. This is consistent with previous observations that herpesvirus phylogenetic branching resembles that of its hosts [ 27 , 33 – 35 ].…”
Section: Case Presentationsupporting
confidence: 93%
“…Standard precautions were taken to prevent cross-contamination of samples. Negative controls for DNA extraction and PCR reactions were conducted in the absence of template and using a previously tested negative sample, while positive reactions were conducted using known herpesvirus DNA obtained from walrus [ 27 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…Two gammaherpesvirus sequences were detected, widening the host range of herpesvirus in pinnipeds. No intranuclear inclusion bodies were observed on histopathology, similarly to other reports of herpesvirus infections in pinnipeds (MELERO et al, 2014;SACRISTÁN et al, 2018). According to the International Committee on Taxonomy of Viruses for herpesviruses (DAVISON et al, 2005), the observed nucleotide and amino acid identities suggest the gammaherpesvirus sequence MH921584 could be classified as a novel species, proposed here as Otariid herpesvirus 7, while the other sequence (MH921583) was possibly a different OtHV-5 strain.…”
Section: Introductionsupporting
confidence: 83%
“…Tattoo skin disease (TSD) is a poxviral cetacean disease. Poxviruses are large DNA viruses infecting humans and several domestic and wild animal species ( 1 , 2 ). Limited available sequencing of Cetacean Poxvirus (CePV) isolates places them in an unclassified genus within the Chordopoxvirinae subfamily, which includes at least two groups: Cetacean Poxvirus type 1 (CePV-1) in odontocetes and CePV-2 in mysticetes ( 3 ).…”
mentioning
confidence: 99%